The Impact of Gross Domestic Producton Macroeconomic Factors Evidence from Pakistan - Alam, Isbat (International Journal of Psychosocial Rehabilitation, 2020)
The key objective of this study is to examine the association amongst the GDP and with macro factors such as BM (Broad money) and inflation. Used time series annually data set from 1977 to 2019 respectively. Multiple regression method is utilized to investigate the significance of the variables with GDP. Heteroskedasity and serial correlation valuation are utilized investigate the residuals normality as well as correctness of the data series variables. This analysis observes that BM and inflation both are significant positively at 1% of level. That’s shows positive significant causality with GDP. This study encourages the public, stock exchanges and investors.